2019
DOI: 10.1213/ane.0000000000004127
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning Prevents Postoperative Acute Kidney Injury After Open Total Aortic Arch Replacement: A Double-Blind, Randomized, Sham-Controlled Trial

Abstract: BACKGROUND: Acute kidney injury is a common complication after open total aortic arch replacement but lacks effective preventive strategies. Remote ischemic preconditioning has controversial results of its benefit to the kidney and may perform better in high-risk patients of acute kidney injury. We investigated whether remote ischemic preconditioning would prevent postoperative acute kidney injury after open total aortic arch replacement. METHODS: We en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 33 publications
2
31
3
Order By: Relevance
“…The 90-day follow-up study of Zarbock et al [8] had the same clinical endpoint as our study, but the results of the two studies were contrary. A possible explanation was that 74 patients had CKD before surgery in the study of Zarbock et al [7], whereas there was only one patient with CKD before surgery in our study [11]. In addition, patients with comorbidities such as hypertension and diabetes mellitus make it di cult to recover from AKI [17].…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…The 90-day follow-up study of Zarbock et al [8] had the same clinical endpoint as our study, but the results of the two studies were contrary. A possible explanation was that 74 patients had CKD before surgery in the study of Zarbock et al [7], whereas there was only one patient with CKD before surgery in our study [11]. In addition, patients with comorbidities such as hypertension and diabetes mellitus make it di cult to recover from AKI [17].…”
Section: Discussionmentioning
confidence: 68%
“…In total, 130 patients were included in our 90-day analysis, and data were available for all study participants, as shown in Figure 1. We have previously revealed the baseline and operative features of patients in the groups, and there were no relevant imbalances between the two groups at baseline [11].…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations